Fundamentals Of Entrepreneurship (ENT300) : Coffee Bean and tea leaf (CBTL) / Izzat Muqri Mohamad ... [et al.] - Mohamad, Izzat Muqri; Saipol, Mohamad Shafiq Shariz; Suhaimi, Muhammad Azizan (2017)
Based on the interview that we have done, we can know more about the business company information. We obtain many information about the company from the Assistant Manager. The informat ion that we get is such as when the stores staned their operation, their target customer, business strategy the employee and the financial achievement that the company get. Next, on company analysis, we use the Strength, Weakness, Opportunities and Threat (SWOT) analysis to find the advantages and the disadvantages of their ongoing business. From this SWOT analysis, wc will know how far this business can overcome their problem and bow far they can use their strength and opportunities to improve their business based on services and others. From (SWOT) we also can see how the company can handle their weakness and threat properly so that it will not affect ther business.